Southampton Arm Fracture Frailty and Sarcopenia Study (SAFFSS): a study protocol for the feasibility of assessing frailty and sarcopenia among older patients with an upper limb fracture - Shihua Zhu; Guiqing Lily Yao; Helen C Roberts; Kinda Ibrahim; Mark Mullee; Mark Baxter; Simon Tilly; Cynthia Russell (BMJ Open)
Introduction Falls are a major health problem for older people; 35% of people aged 65+ years fall every year, leading to fractures in 10%–15%. Upper limb fractures are often the first sign of osteoporosis and routine screening for osteoporosis is recommended by the National Institute for Health and Care Excellence to prevent subsequent hip fractures. However, both frailty and sarcopenia (muscle weakness) are associated with increased risk of falling and fracture but are not routinely identified in this group. The aim of this study is to evaluate the feasibility of assessing and managing frailty and sarcopenia among people aged 65+ years with an upper limb fracture.Methods and analysis This study will be conducted in three fracture clinics in one acute trust in England. 100 people aged 65+ years with an upper arm fracture will be recruited and assessed using six validated frailty measures and two sarcopenia tools. The prevalence of the two conditions and the best tools to use will be determined. Those with either condition will be referred to geriatric clinical teams for comprehensive geriatric assessment (CGA). We will document the proportion who are referred for CGA and those who receive CGA. Other outcome measures including falls, fractures and healthcare resource use over 6 months will be collected. In-depth interviews with a purposive sample of patients who undergo the frailty and sarcopenia assessments and healthcare professionals in fracture clinics and geriatric services will be carried out to their acceptability of assessing frailty and sarcopenia in a busy environment.Ethics and dissemination The study was given the relevant ethical approvals from NHS Research Ethics Committee (REC No: 18/NE/0377), the University Hospital Southampton NHS Foundation Trust, and the University of Southampton, Faculty of Medicine Ethics Committee and Research Governance Office. Findings will be published in scientific journals and presented to local, national and international conferences.Trial registration number ISRCTN13848445